2005
DOI: 10.1136/jmg.2005.031385
|View full text |Cite
|
Sign up to set email alerts
|

Cleft lip/palate and CDH1/E-cadherin mutations in families with hereditary diffuse gastric cancer

Abstract: We report the association of CDH1/E-cadherin mutations with cleft lip, with or without cleft palate (CLP), in two families with hereditary diffuse gastric cancer (HDGC). In each family, the CDH1 mutation was a splicing mutation generating aberrant transcripts with an in-frame deletion, removing the extracellular cadherin repeat domains involved in cell-cell adhesion. Such transcripts might encode mutant proteins with trans-dominant negative effects. We found that CDH1 is highly expressed at 4 and 5 weeks in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
145
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(159 citation statements)
references
References 16 publications
(9 reference statements)
3
145
1
3
Order By: Relevance
“…Genetic alterations, as LOH, which seem to be acquired later in HDGC progression, could be then targeted with drugs such as EGFR and ␣5-␤1-integrinblocking antibodies or transforming growth factor-␤-R small synthetic molecules to prevent cells from migrating and metastasis from establishing. [35][36][37][38][39][40] In conclusion, our data support the previously published rate of CDH1 promoter hypermethylation as a 2nd-hit in HDGC primary tumors, and adds LOH as a key mechanism, mainly in metastatic lesions. Because of the concomitance and heterogeneity of these alterations in neoplastic lesions and the plasticity of hypermethylated promoters during tumor initiation and progression, drugs targeting only epigenetic alterations might not be effective, particularly in patients with metastatic HDGC.…”
Section: Discussionsupporting
confidence: 91%
“…Genetic alterations, as LOH, which seem to be acquired later in HDGC progression, could be then targeted with drugs such as EGFR and ␣5-␤1-integrinblocking antibodies or transforming growth factor-␤-R small synthetic molecules to prevent cells from migrating and metastasis from establishing. [35][36][37][38][39][40] In conclusion, our data support the previously published rate of CDH1 promoter hypermethylation as a 2nd-hit in HDGC primary tumors, and adds LOH as a key mechanism, mainly in metastatic lesions. Because of the concomitance and heterogeneity of these alterations in neoplastic lesions and the plasticity of hypermethylated promoters during tumor initiation and progression, drugs targeting only epigenetic alterations might not be effective, particularly in patients with metastatic HDGC.…”
Section: Discussionsupporting
confidence: 91%
“…Based on our pedigree structures alone, where most or all distant affected relatives used in WES had unaffected parents, some incomplete penetrance must exist, so we did not extend our calculation of sharing probabilities to include these unaffected relatives. Frebourg et al (2006) first reported two different splicing site mutations in CDH1 in two families where some relatives had CLP and diffuse gastric cancer, while other relatives had only gastric cancer. Studies of polymorphic SNPs in and near CDH1 have shown equivocal evidence of association in casecontrol studies from various populations (Letra et al 2008;Rafighdoost et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Genes for several of these have been identified, including PVRL1 in CLP-ectodermal dysplasia syndrome (CLPED1), P63 in dominant ectrodactyly with ectodermal dysplasia and CLP (EEC) and related syndromes, and IRF6 in Van der Woude syndrome (recently reviewed in Cobourne, 2004;Cox, 2004;Marazita and Mooney, 2004). In addition, mutations in E-cadherin (CDH1) were recently found in two families with hereditary diffuse gastric cancer associated with CLP (Frebourg et al, 2005) and mutations in EFNB1 in craniofrontonasal syndrome (CFNS; Twigg et al, 2004;Wieland et al, 2004). Interestingly, PVRL1, P63, IRF6, and CDH1 are all predominantly expressed in epithelial tissues, indicating that proper epithelial differentiation, organization, or patterning play important roles in lip development.…”
Section: Other Genes and Pathwaysmentioning
confidence: 99%